EFFECT OF GLASS POWDER ON THE MECHANICAL PROPERTIES OF MORTAR - Sameh Zabadi; Taher Sameer; Shaker Alhanbly (My University, 2011)
Summary, conclusions and recommendations. What follows now is a summary of the methodology and results of the conducted research. Waste glass powder is a new supplementary material that can be used in mortar mixtures. In this conducted study, more than 48 mixes of mortar were prepared by using waste glass powder as a replacement for cement or for limestone.  Mechanical properties were tested. The mechanical properties include compressive strength. As described in the result section and the abstract, the results show us that when the limestone is replaced by waste glass powder, the compressive strength will increase because it is a filler. Because the limestone contains a lot of vacuums,  the glass powder serves as  a filler material. On the contrary, when replacing glass powder  with cement, the compressive strength will  decrease. Cement is the main material for the strength of mortar or concrete. Another experiment conducted in this study is the heat flow test. The results show that there is not a significant effect measured  when the glasspowder is replaced with either cement or limestone. There is not a significant difference. The results are very close to eachother and resemble eachother; the obtained results do not differ significantly. Based on the conducted research, the following conclusions can be drawn: Waste glass powder is a relatively new supplementary cementing material, that can be used in the mortar mixtures. It playes a significant role to improve the fresh properties, mechanical properties and durability of mortar. If we use the waste glass powder as a replacement for limestone, the compressive strength of mortar increases significantly. In addition, the maximum compressive strength of mortar can be achieved when using 10% of waste glass powder instead of limestone. There are several recommendations that can be made for future research in this aspect. The usage of  the WGP instead of limestone is an interesting possibility because of the strength .Until now though, there has not been found a way to use it instead of cement, since cement is a major component and material for compressive strength..  Further research in the use of WGP is needed in order to generate the full potential of the waste glass powder.